1981
DOI: 10.1073/pnas.78.8.5071
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonuclease I sensitivity of plasmid genomes in teratocarcinoma-derived stem and differentiated cells.

Abstract: The DNase I (EC 3.1.21.1) sensitivities of the simian virus 40 (SV40) genome, the pBR322 genome, and the herpes simplex virus type 1 thymidine kinase (HSV-1 tk) gene have been compared in teratocarcinoma-derived stem (12-1) and differentiated (12-la) cell lines established by transfection of thymidine Idnase (ATP:thymidine 5'-phosphotransferase, EC 2.7.1.21)-deficient F9 cells with DNA from a tripartite plasmid genome consisting of the pBR322 genome, the SV40 genome, and the HSV The eukaryotic genome is organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…5B, lane 9). We conclude that H-2 and P2-microglobulin genes, like total chromatin and integrated plasmid genomes (10) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5B, lane 9). We conclude that H-2 and P2-microglobulin genes, like total chromatin and integrated plasmid genomes (10) …”
Section: Resultsmentioning
confidence: 99%
“…DNase I digestions were carried out by the procedure of Weintraub and Groudine (21) as described (10) [10][11][12][13][14][15] hr, and DNA was isolated from all samples as described (10).…”
Section: Methodsmentioning
confidence: 99%
“…An alternative to a strict gene regulatory network mechanism of lineage priming or pre-patterning, would be a mechanism involving epigenetic regulation. It has been recognised for many years that pluripotent stem cells have a more open chromatin structure than their differentiated derivatives [32] , perhaps permitting ‘leaky’ gene expression. Much more recently it was reported that in ES cells the histones associated with the chromatin of various developmentally regulated genes, notably transcription factors, show bivalent repressive and activation marks [33] , [34] .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that chromatin in undifferentiated cells is generally sensitive to DNase I digestion (26). The same workers also studied the DNase I sensitivity of transfectionally introduced genes in teratocarcinoma cells and found that these genes are sensitive to the enzyme (12). I tested the DNase I sensitivity of methylated M-MuLV in EC-Al cells and found that the viral sequence in undifferentiated cells was sensitive to DNase I digestion but became resistant to the enzyme in differentiated cells (K. Iwasaki and 0.…”
Section: Discussionmentioning
confidence: 99%